Cross-cultural Competence as Success Factor of Employee Retention? - Stefan Stark (Communications of International Proceedings, 2022)
Purpose: The study aims to provide company managers with a basis for considering the need for company-specific future skills and deriving suitable and sustainable qualification measures from this in good time. Findings and Originality: The study aims to identify current needs and anticipate skills gaps. This should enable companies today to identify and build up the necessary skills of tomorrow. The study can serve as an impetus for a strategic orientation in the human resources policy of companies. In this way, it makes a contribution to ensuring competitiveness in the long term and placing the human factor at the center.
Keywords: Future Competencies; Skills of Tomorrow; Strategic Orientation.